The QuantiPhage assay: A novel method for the rapid colorimetric detection of coliphages using cellulose pad materials. (1st February 2019) - Rames, Emily; Macdonald, Joanne
Abstract: Assessment of viral contamination is essential for monitoring the microbial quality of water and protection of public health, as human virus presence is not accurately determined using bacterial indicators. Currently, the time required for conventional viral testing means that water contaminated with human pathogens may be used (e.g. for drinking, recreation or irrigation) days before results are available. Here we report a new rapid method for coliphage enumeration, the QuantiPhage (QP) assay. The novelty of the assay is the use of cellulose absorbent pad materials to support coliphage growth and colorimetric detection, in place of agar that is used in the plaque assay. In addition to saving time associated with agar preparation and tempering, the QP assay enabled enumeration of somatic coliphages in 1.5–2 h and F+ coliphages in 2.5–3 h. The assays were highly sensitive, with a lower detection limit of 1 plaque forming unit (PFU) per mL where 1 mL sample volumes were analysed, and 1 PFU per 10 mL where 10 mL sample volumes were analysed. This is the first rapid culture assay to enable low numbers of coliphages to be reliably detected and to produce directly equivalent results to agar-based plaque assays. A novel gelatin-immobilisation method is also reported, that reduces time to prepare bacterial cells from ∼20 h to 40–60 min (depending on the assay format), and provides a ready to use form of cells, that is compatible with rapid detection and kit formats. When applied to analysis of somatic coliphages in wastewater samples and surface water samples, mean differences in results of the QP assay and the conventional plaque assay were not statistically significant (mean difference ≤ 0.15 log10 PFU/L and 0.5 PFU/10 mL respectively, P > 0.05). The QP is a valuable tool for assessing microbial water quality, which may assist in improving the management of water resources. Graphical abstract: Image 1 Highlights: Rapid, sensitive (1 PFU/10 mL) and simple culture method for enumerating coliphages. Somatic coliphages can be detected in 1.5 h (>100 PFU) to 2 h (1–100 PFU). F+ coliphages can be detected in 2.5 h (>100 PFU) to 3 h (1–100 PFU). Use with freshly cultured or immobilised (ready to use) host bacteria. Equivalent results to the conventional plaque assay, but in a much faster time.